Reviewing the Book L’éducation Cultures et Sociétés - Ali Reza Asareh (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
In his book L’éducation cultures et sociétés, Le Thanh Khoi presents a general and universal theory of education. The book is presented in two parts of " Statement of the Problem ", in three chapters (Theory and Concepts, Generality and Complexity, and Understanding and explanation) and "Providing a General and Universal Model of Education" in 7 chapters (People, Languages ​​and Ethnicities, Natural Environment, the productive system, ideas and values, the role of personalities, the socio-political structures and movements and international relations. Khoi's analysis of psychology was analytic-theoretical- paraphrastic and commentary and all are qualitative methods and of course, sometimes he uses analogy and deduction. In the statistical population of his research, many of the samples lacked the chance of being selected. In some cases, the researcher's deduction and inference were limited by the conceptual definition. The main point in this research is ignoring the methodology concepts and postmodernism paradigms (which is authenticating the qualitative pluralism). Unlike postmodernism, he authenticates the universalist and general frameworks related to the modernism positivism. In addition, the examples presented, his teaching methods and approaches to educators and individuals, etc., affect the traditional and old education and are somewhat distant from new theories and ideas.